Characteristics of Ice Nucleating Particles in and Around California Winter Storms. Issue 21 (14th November 2019) - Levin, Ezra J.T.; DeMott, Paul J.; Suski, Kaitlyn J.; Boose, Yvonne; Hill, Thomas C.J.; McCluskey, Christina S.; Schill, Gregory P.; Rocci, Katherine; Al‐Mashat, Hashim; Kristensen, Louise J.; Cornwell, Gavin; Prather, Kimberly; et al.
Abstract: A major component of California's yearly precipitation comes from wintertime atmospheric river events which bring large amounts of moisture from the tropics up to the midlatitudes. Understanding these systems, specifically the effects of aerosol particles on precipitation associated with these storms, was a major focus of the 2015 Atmospheric Radiation Measurement Cloud Aerosol Precipitation Experiment, which was part of the wintertime California Water 2015 campaign. The measurement campaign provided sampling platforms on four aircraft, including the Atmospheric Radiation Measurement Aerial Facility G‐1, as well as the National Oceanic and Atmospheric Administration Ronald H. Brown research vessel and at a ground station in Bodega Bay, CA. Measurements of ice nucleating particles (INPs) were made with the Colorado State University Continuous Flow Diffusion Chamber aboard the G‐1, and aerosol filters were collected on the G‐1, at the Bodega Bay site and on the Ronald H. Brown for postprocessing via immersion freezing in the Colorado State University Ice Spectrometer. Aerosol composition was measured aboard the G‐1 with the Aerosol Time‐of‐Flight Mass Spectrometer. Here we present INP concentrations and aerosol chemical compositions during the course of the aircraft campaign. During the atmospheric river event, we found that marine aerosol was the main aerosol type and that marine INPs were dominant at cloud activation temperatures, which is in stark contrast to the dominance of dust INPs during the atmospheric river events in the California Water 2011 campaign. Key Points: Ice nucleating particle number concentrations varied by a factor of 100 or more during a wintertime coastal California aircraft campaign Ice nucleating particle number concentrations in the airmass associated with an atmospheric river were less than 1 per liter at −25 °C Marine aerosol were the likely dominate source of ice nucleating particles for the atmospheric river event